Fate of nitrogen applied to a sesame crop (sesamum indicum l.) in a degraded soil of paraguay (2014)
In Paraguay sesame (Sesamum indicum L.) is becoming less productive due to degradation of soil fertility. Nitrogen fertilization increases yields in soils poor in this nutrient, but little is known about its efficiency. In the study the isotopic technique was used to determine the fate of N applied to a crop of sesame. In the experimental field of the Facultad de Ciencias Agrarias of the Universidad Nacional de Asunción, Paraguay, in a randomized complete block experimental design, it was studied the efficiency in the application of N fertilizer and green manure (lupine + black oat) with and without tillage. Nitrogen was applied as urea-15N (5% enrichment) at 50 kg/ha. The results showed content (kg/ha) of N in grains(84), dry matter (104) and soil to 15 cm (938). The plant absorbed 20% of the applied N, 42% remained in the soil and 38% could not be accounted for and possibly it was lost by leaching and volatilization. The isotope dilution technique was useful in determining the fate of applied N, but overestimated the contribution of green manures on the soil N content.